Effectiveness of an Acute Care for Elders unit at a long-term care facility for frail older patients with COVID-19 - Vallecillo, Gabriel (Geriatr Nurs, 2021)
The Acute Care for Elders (ACE) is a model of care addressed to reduce the incidence of loss of self-care abilities of older adults occurring during hospitalization for acute illness. This observational study aimed to describe the effectiveness of an ACE unit at a long-term care facility to prevent functional decline (decrease in the Barthel Index score of >5 points from admission to discharge) in older adults with frailty (Clinical Frailty Scale score ≥5) and symptomatic COVID-19. Fifty-one patients (mean age: 80.2 + 9.1 years) were included. Twenty-eight (54.9%) were women, with a median Barthel index of 50 (IQR:30–60) and Charlson of 6(IQR: 5–7), and 33 (64.7%) had cognitive impairment. At discharge, 36(70.6%) patients had no functional decline, 6 (11.7%) were transferred to hospital and 4(7.8%) died. An ACE unit at a long-term care facility constitutes an alternative to hospital care to prevent hospital-associated disability for frail older patients with COVID-19.